Developing social entrepreneurship skills in community projects for sustainable development goals - Dagli, Gokmen; Altinay, Zehra; Sharma, Ramesh Chander; Altinay, Fahriye (Asian Development Policy Review, 2025)
This study investigates how social entrepreneurship skills are cultivated among student teachers through participation in community-based projects aligned with the Sustainable Development Goals (SDGs). Employing a qualitative research design, data were collected via semi-structured interviews to explore student teachers’ perceptions of social entrepreneurship, the role of community service, and how such experiences contribute to their skill development. Findings reveal that engaging in these projects enhances students’ sense of responsibility, collaboration, empathy, and innovation. Participants view community service not only as a means to address local needs but also as a platform for fostering sustainable social change and strengthening community bonds. These initiatives enable student teachers to become more socially aware and better equipped to respond to real-world challenges with entrepreneurial thinking. The research highlights the pivotal role of student teachers in shaping future societies and underscores the need to embed social entrepreneurship within teacher education programs. This study offers valuable insights for curriculum developers, policymakers, and educators aiming to align teacher education with global development goals. It advocates for evidence-based, community-focused learning experiences that promote leadership, adaptability, and social innovation key competencies for building inclusive, smart, and sustainable societies.